Atmospheric-ionospheric disturbances following the April 2015 Calbuco volcano from GPS and OMI observations. Issue 12 (15th December 2017) - Liu, Xin; Zhang, Qinyun; Shah, M.; Hong, Z.
Abstract: The atmospheric-ionospheric anomalies triggered by eruptions of the Calbuco volcano on 22th and 23th, April 2015 are investigated from 50 continuous GPS stations observations. Prominent total electron content (TEC) disturbances with the amplitude of 0.1–0.4 TECU are found about one hour after the eruptions. The disturbance lasts more than one hour for the first eruption and about half hour for the second eruption. The disturbance features are extracted from PRN03 and PRN23 for the first eruption and PRN13 and PRN28 for the second eruption. The propagation velocities from the travel time diagrams are around 800 m/s and 900 m/s for the two eruptions, respectively. The spectrogram of filtered TEC time series is centered at 3.7 mHz, which is in the frequency range of infrasonic waves. The distribution and characteristics of the TEC anomalies are closely associated with the position relationship between SIP tracks and volcano. The results of SO2 and temperature anomalies around the eruptions obtained from Aura/Ozone Monitoring Instrument (OMI) and Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) vertical profiles are consistent with results from GPS TEC.